A Novel Placement Technique of S2 Screw (from S2 to Promontorium) and Double Screwing from S2 - Dalbayrak, Sedat; Öğrenci, Ahmet; Akar, Ezgi; Koban, Orkun; Yılmaz, Mesut (Indian Journal of Neurosurgery, 2021)
Since pseudoarthrosis or screw loosening is frequently seen in lumbosacral stabilizations ending in S1, S2 screws are used more frequently to support S1 screws. This study aims to describe a new screw placement technique and location from S2. Revision surgery was applied to the patient who had previously undergone surgery with the rigid instrumentation system and encountered pseudoarthrosis during the follow-up period. Instrumentation was performed from S2 to the promontorium. The patient’s chronic low back pain arising due to pseudoarthrosis was reduced and a strong lumbosacral dynamic instrumentation was performed to the patient. Dual screw placement from S2 and/or screw placement in the S2-promontorium direction is a new alternative to provide a powerful instrumentation.
Keywords: S2 screw technique; sacroiliac joint violation; sacropelvic instrumentation